Biocomposite material using sugarcane bagasse and modified starch for potential packaging in agroindustry - Palanisamy, Visharavidev; Md Ali, Abd Halim; Tamunaidu, Pramila; Rosly, Muhammad Bukhari; Md Huzir, Nurhamieza; Amin, Azlan Nur Rasyid (Penerbit UTM Press, 2024)
The widespread use of petroleum-based plastics in packaging has raised significant environmental concerns due to their non-biodegradability and detrimental ecological impacts. This study explores the development of an eco-friendly biocomposite material using sugarcane bagasse and cassava starch as potential alternatives for agro-industry packaging. The research objectives include characterizing the morphological properties of modified and unmodified sugarcane bagasse, analysing the thermal and physical properties of the resultant biocomposite, and evaluating its potential as a sustainable packaging material. A set of samples experiment were investigated using a constant ratio of distilled water to cassava starch which is 3:1 and 5 different ratios of acetic acid to bagasse. The morphological properties of biocomposite material which are sugarcane bagasse and cassava starch were examined using a FieldEmission Scanning Electron Microscope and Fourier Transmission Infrared Spectroscopy. Thermogravimetric Analysis (TGA) and Tensile strength were used to analyse thermal and physical property. Subsequently, the assessment of environmental friendliness was conducted by biodegradability testing. The results indicate that the most optimal biofilm, in terms of flexibility, thermal stability, and decomposition speed, was achieved with a ratio of (2:1) and (3:1) of acetic acid to bagasse. The results obtained suggest that sugarcane bagasse, when combined with cassava starch, can serve as an effective, biodegradable packaging material, potentially mitigating the environmental impact of conventional plastics in the agro-industry.